Strategy of Traditional Blood Cockle Farming in Limau Kapas District, Riau Province: A Value Chain and Governance Framework Analysis - Nyoto Nyoto; Irwan Effendi; Evi Deliana; Emilda Firdaus; Hanafi Hussin (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The traditional blood cockle farm in Limau Kapas District, Riau Province, Indonesia, has high economic potency, yet it still needs to be developed. While it has great potential, this sector faces a range of long-held challenges (particularly vague regulations that hinder legal-based businesses and repeated claims of land ownership from local fishermen who often steal fish from harvests). Objective: To investigate the economic opportunities that can be achieved by adopting good governance and improving management capabilities. Methods: The research was conducted using the qualitative method, with observation, interviews, and a literature review. Results: The results suggest that improved governance can play a large role in alleviating these problems and increasing productivity. A collaborative effort between the government and the local community is key to developing a sustainable aquaculture ecosystem through education, favorable legislation, and access to capital for farmers. To gain those economic benefits of blood cockle aquaculture in the area, it is necessary to strengthen these aspects. Conclusion: In conclusion, traditional blood cockle farming in the Limau Kapas District has great economic prospects but is hindered by governance gaps, regulatory ambiguity and limited access to finance. Sustainable and equitable aquaculture development is possible only through effective institutional collaboration between government, universities, and local communities.